Evaluation Challenges And Directions For Information Seeking Support Systems - Kelly, Diane; Dumais, Susan; Pedersen, Jan O. (IEEE Computer, 2009)
ISSSs provide an exciting opportunity to extend previous information-seeking and interactive IR evaluation models and create a research community that embraces diverse methods and broader participation.